The role of helminths in the development of non-communicable diseases - Wu, Yifan; Duffey, Megan; Alex, Saira Elizabeth; Suarez-Reyes, Charlie; Clark, Eva H.; Weatherhead, Jill E. (Frontiers in Immunology, 2022)
Non-communicable diseases (NCDs) like cardiovascular disease, chronic respiratory diseases, cancers, diabetes, and neuropsychiatric diseases cause significant global morbidity and mortality which disproportionately affect those living in low resource regions including low- and middle-income countries (LMICs). In order to reduce NCD morbidity and mortality in LMIC it is imperative to understand risk factors associated with the development of NCDs. Certain infections are known risk factors for many NCDs. Several parasitic helminth infections, which occur most commonly in LMICs, have been identified as potential drivers of NCDs in parasite-endemic regions. Though understudied, the impact of helminth infections on the development of NCDs is likely related to helminth-specific factors, including species, developmental stage and disease burden. Mechanical and chemical damage induced by the helminth in combination with pathologic host immune responses contribute to the long-term inflammation that increases risk for NCD development. Robust studies from animal models and human clinical trials are needed to understand the immunologic mechanisms of helminth-induced NCDs. Understanding the complex connection between helminths and NCDs will aid in targeted public health programs to reduce helminth-induced NCDs and reduce the high rates of morbidity that affects millions of people living in parasite-endemic, LMICs globally.